Phyllody Disease of Parthenium Weed in Ethiopia - Taye Tessema; C Obermeier; G Einhorn; E Seemuller; C Biittner (Pest Managment Journal of Ethiopia, 2023)
Parthenium hysterophorus L. (Compositae, Helianthae) is an exotic invasive weed currently occurring widely in Ethiopia, India and Australia. Studies on the detection of the parthenium phyllody disease-causing agent, incidence and distribution in the field were carried out during 1999-2002. The disease was commonly observed in low-to-middle altitude areas (900-2350 m.) of Ethiopia with an incidence reaching 75%. The phyllody-infected plants were characterised by excessive branching, reduced plant height, leaf size, and transformation of floral structures into leaf-like structures that lead to sterility. Phyllody-diseased plants were examined for phytoplasma infection by means of Polymerase Chain Reaction (PCR) using universal primers P1 and P7. PCR products of about 1800 bp were obtained after amplification of DNA isolated from fresh and dried parthenium specimens showing phyllody symptoms. Digestion with Alul restriction enzyme revealed restriction patterns for all samples corresponding to patterns typically observed for the faba bean phyllody (FBP) phytoplasma group. A phytoplasma was also obtained from a suspected insect vector, Tylorilygus apicalus, which was not identical with the phytoplasma DNA obtained from a diseased plant. Analysis of the electron microscope photographs also showed pleomorphic phytoplasma-like bodies of different sizes and shapes. The susceptibility of parthenium to phyllody disease may, therefore, be utilised as a classical biological control of parthenium after assessing the potential benefits and risks.